Architecture and Physical Activity: A Systematic Review - Yan , Mun Hei; Mohd Salleh, Mohd Najib (MAJ - Malaysia Architectural Journal, 2020)
Malaysia is facing obesity epidemic like the other developing country for the last decade, obesity is one of the major cause to the Non-Communicable Disease and was found that NDC causes the increase of mortality rate in Malaysia. The advancement of technology, humans are relying a lot on technology and resulted in sedentary lifestyle. Hence, the built environment is an important in promoting physical activity as human spend most of te time in built environment. A systematic search of research paper, journals and articles from the year of 2002 to 2019 are studied to investigate the relationship between built environment and the physical activity. The findings of the review shows that the built environment attributes such as, connectivity of streets, availability of pedestrian walkway, parks, recreational facilities are positively correlates with the physical activities in human daily life. The social environment of perceived safety in the neighbourhood that have positive affect on human physical activity. Built environment can be utilized to encourage and promote physical activity among Malaysians by improvising the walkability and connection in the neighbourhood, parks and playground, and the availability of recreational facilities. Further research and investigation on architecture intervention should be done to achieve the goal of increasing the physical health of Malaysians